2021
DOI: 10.3389/fimmu.2021.772570
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of Dietary Mannan Oligosaccharides on Non-Specific Immunity, Intestinal Health, and Antibiotic Resistance Genes in Pacific White Shrimp Litopenaeus vannamei

Abstract: This study was conducted to comprehensively investigate the beneficial effects of a mannan oligosaccharide product (hereinafter called MOS) on Litopenaeus vannamei and optimum level of MOS. Five isonitrogenous and isolipid diets were formulated by adding 0%, 0.02%, 0.04%, 0.08%, and 0.16% MOS in the basal diet. Each diet was randomly fed to one group with four replicates of shrimp in an 8-week feeding trial. The results showed that dietary MOS improved the growth performance and the ability of digestion of shr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 62 publications
(78 reference statements)
1
7
0
Order By: Relevance
“…Few studies have reported the effects of zinc on intestinal microbiota in shrimp. The present study found that Firmicutes, Proteobacteria and Bacteroidota were the predominant phyla, and Candidatus_Bacilloplasma , Vibrio and Spongiimonas were the predominant genera, which is consistent with previous results in shrimp [ 80 , 81 ]. Moreover, the cluster results showed that the microbiota community was migrated by the dosage of organic zinc, especially in the O60, O90 and O120 groups, since the top 10 bacteria were similar among all groups and alpha diversity did not differ greatly.…”
Section: Discussionsupporting
confidence: 93%
“…Few studies have reported the effects of zinc on intestinal microbiota in shrimp. The present study found that Firmicutes, Proteobacteria and Bacteroidota were the predominant phyla, and Candidatus_Bacilloplasma , Vibrio and Spongiimonas were the predominant genera, which is consistent with previous results in shrimp [ 80 , 81 ]. Moreover, the cluster results showed that the microbiota community was migrated by the dosage of organic zinc, especially in the O60, O90 and O120 groups, since the top 10 bacteria were similar among all groups and alpha diversity did not differ greatly.…”
Section: Discussionsupporting
confidence: 93%
“…Antibiotic resistance has become a serious problem threating global public health (Malhadas et al, 2017;Wang et al, 2021), suggesting roles of new antimicrobial drugs in solving this increasingly serious problem in addition to the proper use of antibiotics. Unfortunately, it has become increasingly…”
Section: Discussionmentioning
confidence: 99%
“…Antibiotic resistance has become a serious problem threating global public health ( Malhadas et al, 2017 ; Wang et al, 2021 ), suggesting roles of new antimicrobial drugs in solving this increasingly serious problem in addition to the proper use of antibiotics. Unfortunately, it has become increasingly difficult to find new antibiotics from the conventional soil environment, resulting in nearly three decades without a new antibiotic ( Böttcher et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…38 In an 8 week feeding trial, shrimp with mannan oligosaccharide supplementation improved their intestinal immunity by increasing IAP activity. 39 Additionally, Caco-2 cells treated with galactose oligosaccharide showed an upregulation in IAP. 40 Together, these results suggest that carbohydrates can effectively increase IAP levels.…”
Section: Nutritional Regulation Of Endogenous Iapmentioning
confidence: 97%
“…Dietary fermentable oligosaccharides increased IAP activity and expression, and mucin and microbial fermentation, thereby maintaining intestinal homeostasis . In an 8 week feeding trial, shrimp with mannan oligosaccharide supplementation improved their intestinal immunity by increasing IAP activity . Additionally, Caco-2 cells treated with galactose oligosaccharide showed an upregulation in IAP .…”
Section: Nutritional Regulation Of Endogenous Iapmentioning
confidence: 97%